The DUMASS: AR-based Learning Media Innovation in Recognizing German Culture, History and Geographical Conditions - Li'munawar, Istiqlal Masfirotul; Catur, Davi Aniska; Purwantini, Lellyana; Panjalu, Muhammad Farrel (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
The use of technology has been very attached to humans, both from young people, and even the elderly. With the development of existing technology, Augmented Reality (AR) is one of the technologies that are trending and widely used. Augmented Reality itself has many benefits that can be applied to various fields. In the field of education, AR can be applied to be a fun learning media because it attracts attention from the visualization that is generated. In addition, AR is also a solution for users who find it difficult to learn about German statehood and culture. Dumass (Deutsch Macht Spass) is a learning media product combining books and Augmented Reality (AR) technology which contains material about Kulturkunde (culture) and Landeskunde (geographical layout), also in the A1 language level (Niveau A1) which can be used by ordinary learners to get to know German. With the use of AR technology assisted by the QR Code feature, it is hoped that it can provide an overview to readers about the German state in real life. This AR is supported by a QR Code that will realize images or explanations so that they look more real.